The pigman : a novel - Zindel, Paul. (New York : HarperCollins, 1968)
A teenage boy and a girl, high school sophomores from unhappy homes, tell of their bizzare relationship with an old man.
Notable/Best Books (A.L.A.).
Wilson's Junior High School.
Wilson's Senior High School.
5.9
Young Adult.
Young Adult
Keywords: Friendship -- Fiction; Friendship -- Fiction